Structures and dynamics of g-quadruplexes formed by human CEB1 and CEB25 minisatellites - Adrian, Michael (2014)
G-quadruplex is a family of non-canonical DNA which has been gaining popularity due to mounting evidence of its biological function, promising therapeutic prospect and potential application in nanotechnology. These four-stranded polymorphic structures are formed by G-rich nucleic acid sequences. As part of genome, G-quadruplex-forming minisatellites are associated with high degree of polymorphism and have been shown to interact with specific protein and ligand. This research addresses conformational diversity originated from human minisatellite sequences through combination of biophysical techniques. Several G-quadruplexes are identified from mutable CEB1 sequence. In particular, a dimeric G-quadruplex with unique dynamic property is investigated thoroughly. G-quadruplex solution structures from CEB1 and CEB25 sequences are elucidated using NMR spectroscopy. Moreover, the formation of monomorphic G-quadruplexes on a long single-stranded CEB25 sequence is demonstrated. Subsequently, the role of these G-quadruplexes towards genomic instability is examined in model organism yeast: (i) multiple G-quadruplexes are shown to destabilize CEB1 allele in a cooperative manner and (ii) G-quadruplex loop length and thermal stability are important to the instability of CEB25 allele. In addition, the study of local motions occurring within G-quadruplex molecules is initiated on known structures, highlighting the effect of base stacking and ligand binding on rotational dynamics of amino group. The findings presented in this thesis add to the basic understanding of the formation of multiple G-quadruplexes within a nucleic acid sequence and, coupled with mutagenesis study, may provide insights on the molecular mechanism of G-quadruplex interaction with endogenous protein and stabilizing ligand.